Inflammatory myofibroblastic tumour of the lung: a reactive lesion or a true neoplasm? - Panagiotopoulos, Nikolaos (J Thorac Dis, 2015)
Inflammatory myofibroblastic tumour (IMT) of the lung represents an extremely rare type of inflammatory pseudo tumor that appears most commonly in children and young individuals. There has been an ongoing controversy whether an IMT is a reactive lesion or a true neoplasm making the further management extremely challenging. Purpose of the paper is through a literature review to highlight the existence of this rare tumour along with its key features and the management options available.